Osteogenic potential in Piper sarmentosum Roxb.: a systematic review of in vitro and in vivo evidence - Intan Zarina Zainol Abidin,; Aliwaisi, Roa M.A.; Yamamoto, Zulham; Muhammad Dain Yazid,; Shahrul Hisham Zainal Ariffin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Piper sarmentosum Roxb. (Ps) has various therapeutic properties, however, the in vitro and in vivo effects on bone health, suitable dosage, and involvement of key metabolites remain unclear. This systematic review aims to evaluate Ps role in bone formation, dosage considerations, and active metabolites, highlighting the potential in future bone health therapy. The search was conducted in PubMed (Medline), Scopus, and Web of Science databases from 2014-2025. Related original articles published in English were included, while duplicates, secondary, and unrelated sources were excluded. Six articles from 1,523 met the inclusion criteria, and two additional eligible articles were manually selected from the reference lists, bringing the total to eight articles. Four studies used in vivo glucocorticoid-induced osteoporotic Sprague-Dawley rat models, while one employed an in vivo zebrafish model. The in vitro study involved two human Peripheral Blood Stem Cells and one MC3T3-E1 cell-line. The articles showed osteoprotective effects, particularly in glucocorticoid-induced models. Leaf extracts improved bone microstructure and osteoblast activity both in vitro and in vivo, evidenced by increased OPG mRNA expression, reduced RANKL/OPG mRNA expression ratio, enhanced mineralization, upregulation of osteoblast gene markers, and antioxidant activity with asarone and gamma-asarone as potential metabolites. Ps extract promotes osteoblast differentiation and bone formation in vitro and in vivo. In vivo effective dosage is 125 mg/kg/day in rats and 100-400 μg/mL in zebrafish, while 1-50 μg/mL for in vitro. Metabolites such as asarone and gamma-asarone need further investigation to clarify their role in bone health.